SOSIALISASI DAN EDUKASI PENGEMBANGAN AGROEKOWISATA LECI DI NEGERI NAKU KECAMATAN LEITIMUR SELATAN KOTA AMBON - Hukom, Zakarias Frans Mores; Mardiatmoko, Gun; Kunu, Peiter J.; Talahaturuson, Abraham; Effendy, Jollanda; Taihuttu, Hermina N. (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2025)
The lychee tree (Litchi chinensis Sonn.) is perennial fruit plant cultivated in yards and gardens on a small or large scale for the development of agro-ecotourism, agribusiness, and fruit agro-industry. In Naku village, lychee tree havenot been cultivated commercially, so the productivity and quality of the fruit are still relatively low. Developing lychee plantations in Naku for commercial purposes as part of an agro-ecotourism package requires a thorough understanding of the sustainable application of appropriate agro-eco-technology. Therefore, increasing the productivity and quality of lychee fruit in Naku requires a program to raise awareness of the potential for lychee agro-ecotourism development. The lychee agro-ecotourism technology package that was socialized in the Community Service activities in Naku village includes material on the potential for developing lychee agro-ecotourism, the function and benefits of lychee trees as agro-ecotourism landscape plants, land conservation and irrigation techniques for lychee, characterization of the Amboneinsis lychee variety and protection. It is hoped that the technology transfer in this socialization activity can be useful in motivating the people of Naku village towards the potential of developing lychee fruit agro-ecotourism which has high economic value and future business opportunities